T Cell/Histiocyte-Rich Large B Cell Lymphoma of the Thymus: A Diagnostic Pitfall - Jie Xu; Xiaojun Wu; Vishnu Reddy (Case Reports in Hematology)
T cell/histiocyte-rich large B cell lymphoma (THRLBCL) is predominantly a nodal disease, with extranodal involvement, such as bone marrow, spleen, and liver. However, primary THRLBCL has never been reported in the thymus in the English literature. Here we report a case of THRLBCL presenting as mediastinal mass and lymphadenopathy. Based on the frozen section diagnosis of “thymoma,” a 12 cm mass was excised. A year later she developed multiple enlarged lymph nodes and pulmonary nodules. Consultant review of the excised mediastinal mass showed scattered large atypical cells that were CD20+ and PAX-5+ and negative for pan-cytokeratin, AE1, and AE3, compatible with THRLBCL and excluding thymoma. The excised lymph nodes were replaced by diffuse infiltrate of small CD3+ lymphocytes and histiocytes with intermingled large CD20+ B lymphoma cells scattered throughout the section. A diagnosis of THRLBCL was made in lymph node, similar to previous thymic lesion. A clonal rearrangement of immunoglobulin heavy chain (IGH) gene was detected, further supporting the diagnosis. This is the first reported case of THRLBCL in thymus. Correct recognition of this entity is critical, because of the difference in therapeutic impact on these patients.